A qualitative study of parental caregiving experience in adolescents with depression from the perspective of positive psychology in China - Yueyan Zhao; Qunfang Miao; Siying Xin; Peiqing Li; Yaoyao Huang (Frontiers in Public Health)
ObjectiveTo explore the inner experiences and needs of parents of adolescents with depression in the caregiving process, to understand the problems they encounter, and to provide precise intervention and support strategies for this group from a positive psychology orientation.MethodsUse of qualitative research methods, semi-structured interviews were conducted with 12 parents of adolescents with depression, selected from December 2022 to October 2023. Colaizzi′s seven-step analysis method was used to extract themes.ResultsThe parental caregiving experience for adolescents with depression can be grouped into 3 themes and 8 sub-themes: ① Complex negative emotions (negative emotions at the beginning of diagnosis, negative emotions during the caregiving process); ② Adversity experienced by individuals and families (increased physical and financial burdens, lack of access to professional support information, family dysfunction); ③ Coping and adaptation to adversity (self-growth, actively seeking outside assistance, enhanced family connection).ConclusionParents of adolescents with depression have complex caregiving experiences and face numerous difficulties and challenges at different stages of treatment. Caregivers and medical social workers should focus on the inner experiences and needs of parents at various stages of caregiving. Establishment of a joint care model with a positive psychology perspective to enhance individual and family psychological resilience and a sense of disease benefit.